Factors associated with body weight status among adolescents in Bandar Baru Bangi, Selangor - Siti Norhafiza Md Yasin
Childhood obesity has been growing at an alarming rate and is the most common nutritional problem among children in developed as well as in developing countries. This cross-sectional study aimed to determine factors associated with body weight status among adolescents in Bandar Baru Bangi, Selangor. A total number of 120 students (50% male and 50% female respondents) aged 13 to 16 years old had been chosen randomly from two schools in Bandar Baru Bangi namely SMK Jalan Tiga and SMK Jalan Empat to participate in the study. A selfadministered questionnaire which consists.of four sections: socio-demographic, anthropometry, physical activity and dietary intake were distributed to each respondent. The anthropometry measurement of body weight and height were measured using TANITA digital weighing scale and a SECA body meter. Body mass index (BMI) was calculated and further categorised into BMI-for-age. The physical activity level was assessed using a modified form of International Physical Activity Questionnaires (IPAQ). Level of physical activity of the respondents were classified into low (MET- min/week <600), moderate (MET- min/week ≥600) and high (MET- min/week ≥3000) category. The dietary intake of the respondents was assessed using two day 24-hour dietary recall. Results showed majority of the subjects had normal weight (48.3%), followed by 30.8% underweight and 20.9 %were overweight. The mean BMI was 21.71±5.17 kgm-² with female had significantly higher BMI (22.34 kg/m²) as compared to male (21.07±4.91) (t= 117.0, p<0.05). Further categorisation into BMI-for-age found that, majority of the respondents were normal weight (81.7%) followed by obesity (15.0%) and thinness (3.3%). More than half (55.0%) of the respondents were moderately active, 27.5% active and 17.5% were inactive. Male respondent (41.7%) were more physically active than female (13.3%) (χ²=12.59, p<0.05). However, there is no significant association between physical activity level with body weight status (χ²=7.891, p= 0.09). The mean of total daily energy intake was 2062±669 kcal with male respondents (2110±643) had higher energy intake as compared to female (2015±695). Calorie intake was found to have significant association with body weight status (χ²=2.762, p= 0.04). In conclusion, the increasing prevalence of overnutrition reflects a need for intervention program that focus on promoting healthy eating practices and physical activity to further educate adolescents to achieve healthy body weight.